Factors affecting mortality in patients with burns. Issue 3 (2015) - Erbiş, Halil; Aliosmanoglu, Ibrahim; Ozturk, Bunyamin; Ülger, Burak Veli; Timucin, Huseyin; Turkoglu, Mehmet Akif; Vural, Veli
No abstract available